The Relationships of Workplace Spirituality and Psychological Capital with Work Engagement Among Junior High School Teachers - Shwu-Ming Wu (Behavioral Sciences)
Engaged teachers demonstrate high levels of motivation and commitment to their work, increasing the likelihood of job retention and enabling them to perform at their best, ultimately benefiting both schools and students. Teacher engagement may be fostered by enhancing workplace spirituality and psychological capital. This study aimed to examine the relationships between and effects of workplace spirituality and psychological capital on work engagement, while also comparing demographic differences affecting these variables. A sample of 123 teachers was recruited from various junior high schools in Taiwan. The measured variables were workplace spirituality (including meaningful work, inner life, and sense of community), psychological capital (covering efficacy, hope, optimism, and resilience), and work engagement (comprising vigor, dedication, and absorption). The results indicate that male teachers exhibited higher levels of hope and overall psychological capital, while older teachers displayed greater optimism and a stronger sense of community. Additionally, strong positive correlations were found among workplace spirituality, psychological capital, and work engagement. Particularly, workplace spirituality and psychological capital were identified as significant predictors of work engagement among junior high school teachers. The implication for school organizations is that enhancing workplace spirituality and psychological capital should be prioritized as strategies to promote work engagement among junior high school teachers.